Nano-Scale Hydroxyapatite: Synthesis, Two-Dimensional Transport Experiments, and Application for Uranium Remediation - S. R. Kanel; T. P. Clement; M. O. Barnett; M. N. Goltz (Journal of Nanotechnology)
Synthetic nano-scale hydroxyapatite (NHA) was prepared and characterized using X-ray diffraction (XRD) and scanning electron microscopy (SEM) methods. The XRD data confirmed that the crystalline structure and chemical composition of NHA correspond to Ca5OH(PO4)3. The SEM data confirmed the size of NHA to be less than 50 nm. A two-dimensional physical model packed with saturated porous media was used to study the transport characteristics of NHA under constant flow conditions. The data show that the transport patterns of NHA were almost identical to tracer transport patterns. This result indicates that the NHA material can move with water like a tracer, and its movement was neither retarded nor influenced by any physicochemical interactions and/or density effects. We have also tested the reactivity of NHA with 1 mg/L hexavalent uranium (U(VI)) and found that complete removal of U(VI) is possible using 0.5 g/L NHA at pH 5 to 6. Our results demonstrate that NHA has the potential to be injected as a dilute slurry for in situ treatment of U(VI)-contaminated groundwater systems.